MicroRNAs in adipose tissue fibrosis: Mechanisms and therapeutic potential - Mei Tian; Yang Zhou; Yitong Guo; Qing Xia; Zehua Wang; Xinying Zheng; Jinze Shen; Junping Guo; Shiwei Duan; Lijun Wang (Genes and Diseases)
Adipose tissue fibrosis, characterized by abnormal extracellular matrix deposition within adipose tissue, signifies a crucial indicator of adipose tissue malfunction, potentially leading to organ tissue dysfunction. Various factors, including a high-fat diet, non-alcoholic fatty liver disease, and insulin resistance, coincide with adipose tissue fibrosis. MicroRNAs (miRNAs) represent a class of small non-coding RNAs with significant influence on tissue fibrosis through diverse signaling pathways. For instance, in response to a high-fat diet, miRNAs can modulate signaling pathways such as TGF-β/Smad, PI3K/AKT, and PPAR-γ to impact adipose tissue fibrosis. Furthermore, miRNAs play roles in inhibiting fibrosis in different contexts: suppressing corneal fibrosis via the TGF-β/Smad pathway, mitigating cardiac fibrosis through the VEGF signaling pathway, reducing wound fibrosis via regulation of the MAPK signaling pathway, and diminishing fibrosis post-fat transplantation via involvement in the PDGFR-β signaling pathway. Notably, the secretome released by miRNA-transfected adipose-derived stem cells facilitates targeted delivery of miRNAs to evade host immune rejection, enhancing their anti-fibrotic efficacy. Hence, this study endeavors to elucidate the role and mechanism of miRNAs in adipose tissue fibrosis and explore the mechanisms and advantages of the secretome released by miRNA-transfected adipose-derived stem cells in combating fibrotic diseases.